Antioxidants as a Potential Preventive and Therapeutic Strategy for Cadmium - M. Brzóska, Malgorzata; Borowska, Sylwia; Tomczyk, Michal (Current Drug Targets, 2016)
Epidemiological studies provide a growing number of evidences that chronic exposure to relatively low levels of cadmium (Cd), nowadays taking place in industrialized countries, may cause health hazard. Thus, growing interest has been focused on effective ways of protection from adverse effects of exposure to this heavy metal. Because numerous effects to Cd’s toxic action result from its prooxidative properties, it seems reasonable that special attention should be directed to agents that can prevent or reduce this metal-induced oxidative stress and its consequences in tissues, organs and systems at risk of toxicity, including liver, kidneys, testes, ears, eyes, cardiovascular system and nervous system as well as bone tissue. This review discusses a wide range of natural (plant and animal origin) and synthetic antioxidants together with many plant extracts (e.g. black and green tea, Aronia melanocarpa, Allium sativum, Allium cepa, Ocimum sanctum, Phoenix dactylifera, Physalis peruviana, Zingiber officinale) that have been shown to prevent from Cd toxicity. Moreover, some attention has been focused on the fact that substances not possessing antioxidative potential may also prevent Cd-induced oxidative stress and its consequences. So far, most of the data on the protective effects of the natural and synthetic antioxidants and plant extracts come from studies in animals’ models; however, numerous of them seem to be promising preventive/therapeutic strategies for Cd toxicity in humans. Further investigation of prophylactic and therapeutic use of antioxidants in populations exposed to Cd environmentally and occupationally is warranted, given that therapeutically effective chelation therapy for this toxic metal is currently lacking.
Keywords: plant extracts